Comparison of Analytical Hierarchy Process and Analytical Network Process Methods In Determining The Best Tourist Attractions In West Sumatra Province - Kana Kurnia; M. Bryant Rama; Triyawan Bagus Subakja; Syukri Sastrawan; Yogi Septiandri; Muhammad Igo Ilham (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
A tourist attraction is a place visited for its natural beauty, culture, history, or recreation, such as beaches, mountains, national parks, historical buildings, museums, and amusement parks. Each has its unique charm, with some becoming iconic symbols and major tourist destinations. Tourist attractions are vital to the tourism industry, boosting economic growth and preserving cultural and natural heritage.West Sumatra is one of the provinces in Indonesia that is rich in natural and cultural beauty. In an effort to develop the tourism industry in this area, the selection of the right tourist sites is very important. There are 5 references in determining the best tourist attractions in West Sumatra Province, which include Natural Beauty, Cultural Diversity, Infrastructure, Price, and Cleanliness. Meanwhile, there are 5 alternatives that are used as references in determining the best tourist attractions in West Sumatra Province, namely Padang Beach, Carocok Beach, Sianok Gorge, Harau Valley, and Anai Valley. From the experiments that have been carried out, the rank changes that occur with the AHP and ANP methods are shown in Table 13. It can be seen that the AHP method has a higher percentage of sensitivity with a total percentage of 0.25% compared to the percentage of 0.14% in the ANP method. This proves that the AHP method is better than the ANP method for determining tourist attractions in West Sumatra Province.